Reliability, safety, and security of railway systems : modelling, analysis, verification, and certification : first International Conference, RSSRail 2016, Paris, France, June 28-30, 2016, Proceedings /: modelling, analysis, verification, and certification : first International Conference, RSSRail 2016, Paris, France, June 28-30, 2016, Proceedings. (2016) - Unknown
No abstract available